Comparison of the Antimicrobial Activities of Four Honeys From Three Countries (New Zealand, Cuba, and Kenya) - Morroni, Gianluca (Front Microbiol, 2018)
Skin and chronic wound infections are an increasing and urgent health problem worldwide. Their management is difficult and the development of antibiotic resistance by both planktonic and biofilm-associated bacteria necessitates the use of alternative treatments. The purpose of this study was to compare the antimicrobial activity of four honeys from different floral and geographical origins: Melipona beecheii honey (Cuba) and three Apis mellifera honeys [Manuka honey (New Zealand), A. mellifera honey (Cuba), and African honey (Kenya)]. The physicochemical parameters were within the ranges reported for these honeys and M. beecheii honey stood out due to its acidic character. An agar incorporation technique was used to determine the minimum active dilution of each honey against 52 clinical isolates (34 Gram-positive, 17 Gram-negative, and 1 Candida albicans). The antibiofilm activity of honeys was tested by assessing their ability to inhibit biofilm formation and to disrupt preformed biofilms. Overall, M. beecheii honey had the highest antimicrobial and antibiofilm activity, although a marked disruption in preformed biofilms was shared by all tested honeys. Structural changes induced by M. beecheii honey on Staphylococcus aureus and Pseudomonas aeruginosa cells were observed by transmission electron microscopy suggesting that this honey has a potent antimicrobial action and may be an excellent candidate for the development of topical preparations for the treatment of infected wounds.